Proprietary Medicines Containing Bupleurum chinense DC. (Chaihu) for Depression: Network Meta-Analysis and Network Pharmacology Prediction - Li, Qiao-feng; Lu, Wen-tian; Zhang, Qing; Zhao, Yan-dong; Wu, Cheng-yu; Zhou, Hui-fang (Frontiers in Pharmacology, 2022)
Background and Aims: Suicide rates, incidence and recurrence of depression is gradually increasing in recent years. Proprietary Chinese medicines containing Bupleurum chinense DC. (Chaihu) are widely used in clinical practice. This study aimed at evaluating the efficacy and safety of oral proprietary Chinese medicines containing Chaihu for treating depression and exploring the potential pharmacological mechanisms. Methods: This study searched for clinical randomized controlled trial studies (RCTs) about Chaihu-containing products alone or in combination with three classes of commonly used antidepressants. The search deadline is from data inception to April 2021. For efficacy assessment, the clinical response rate, the Hamilton Depression Scale-17 (HAMD-17), and adverse reactions were calculated. Subsequently, the optimal drug obtained from the NMA results, Danzhi Xiaoyao pill (DZXY), was used to conduct network pharmacology analysis. We searched databases to acquire bioactives and potential targets of DZXY and depression-related targets. The protein-protein interaction (PPI) network, component-target network, the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed. Results: The results of the NMA demonstrated that the top 4 interventions with the best efficiency were Jiawei Xiaoyao + SSRI, DZXY + SNRI, Xiaoyao pill + SSRI, and Jieyu pill + SNRI; the top 4 interventions reducing HAMD score were DZXY + SNRI, JWXY, Jieyu pill and Puyu pill + SNRI; the top 4 interventions with the least adverse effects were Jieyu pill, Anle pill + SSRI, DZXY + SNRI, and Puyu pill + SNRI. 147 active compounds and 248 targets in DZXY were identified, of which 175 overlapping targets related to depression. Bioinformatics analysis revealed that MAPK3, JUN, MAPK14, MYC, MAPK1, etc. could become potential therapeutic targets. MAPK signaling pathway might play an essential role in DZXY against depression. Conclusion: This study suggested that the combination of proprietary Chinese medicines containing Chaihu with antidepressants was generally better than antidepressant treatment. DZXY + SNRI showed significantly better results in efficacy, HAMD scores and safety. The antidepressant effect of DZXY may be related to its regulation of neuroinflammation and apoptosis. Keywords: Bupleurum chinense DC., chaihu, proprietary Chinese medicines, depression, network meta-analysis, network pharmacology